2007
DOI: 10.1055/s-2007-971066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Propylthiouracil Treatment on P Wave Duration and P Wave Dispersion in Patients with Overt Hypertyroidism

Abstract: P wave duration and PWD are found prolonged in hyperthyroid patients and propylthiouracil treatment decreased them effectively. This mechanism may establish how the anti-thyroid treatment may prevent the development of atrial fibrillation in hyperthyroid patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…1). 3 , 7–85 Fourteen of these articles utilized only a computer‐assisted technique for P‐wave evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…1). 3 , 7–85 Fourteen of these articles utilized only a computer‐assisted technique for P‐wave evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Guntekin et al 29 and Katircibasi et al 30 found that maximum P-wave duration and P-wave dispertion were increased in hyperthyroidism and treatment with PTU resulted in improvement in P-wave variables. A study by Aras and colleagues 6 reported that simply measuring P maximum and Pwave dispertion values could identify the patients with high risk for the development of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Aras and colleagues 6 reported that simply measuring P maximum and Pwave dispertion values could identify the patients with high risk for the development of atrial fibrillation. Moreover, Guntekin et al 29 and Katircibasi et al 30 found that maximum P-wave duration and P-wave dispertion were increased in hyperthyroidism and treatment with PTU resulted in improvement in P-wave variables. To the best of our knowledge, the effects of antithyroid therapy on atrial electromechanical coupling assessed by TDI was not studied before.…”
Section: Discussionmentioning
confidence: 98%
“…The major portion of the PR interval includes the P wave duration, and there have been many studies regarding the P wave duration or dispersion related to aging, 18 uncontrolled hypertension, 1 diabetes, 2 or obesity. 19 Furthermore, a prolonged P wave duration and dispersion have been known to be associated with aortic stenosis, 20 mitral stenosis, 21 and coronary artery disease, 3 as well as hyperthyroidism, 22 obstructive sleep apnea, 23 or a higher incidence of AF. 24 In the current study, we found a close association between the PR interval and P wave duration, and a prolonged PR interval predicted the clinical recurrence of AF after catheter ablation.…”
Section: Pr Interval As Prognostic Parameter For Cardiac Disease and Afmentioning
confidence: 99%